2016
DOI: 10.1007/s00223-016-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

Osterix and RUNX2 are Transcriptional Regulators of Sclerostin in Human Bone

Abstract: Sclerostin, encoded by the SOST gene, works as an inhibitor of the Wnt pathway and therefore is an important regulator of bone homeostasis. Due to its potent action as an inhibitor of bone formation, blocking sclerostin activity is the purpose of recently developed anti-osteoporotic treatments. Two bone-specific transcription factors, RUNX2 and OSX, have been shown to interact and co-ordinately regulate the expression of bone-specific genes. Although it has been recently shown that sclerostin is targeted by OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 35 publications
(38 reference statements)
1
41
0
Order By: Relevance
“…Since BET up regulates RUNX2 and OSX gene expression and promotes the synthesis of specific non collagenous bone proteins, like BSP and OPN, it is likely that this nutrient is involved in triggering major events in osteogenesis and bone remodeling, potentially restoring the negatively affected balance of bone remodeling during aging. RUNX2 and OSX are indeed key transcription factors of osteoblastic differentiation which activate the downstream processes of osteoblast maturation [1519]; they also interact and coordinately regulate the expression of bone-specific genes [45]. Moreover, BSP and OPN are two non-collagenous proteins which serve as a matrix-associated signals presenting overlapping and multifunctional activities in bone with effects on bone formation, mineralization and remodeling [44].…”
Section: Discussionmentioning
confidence: 99%
“…Since BET up regulates RUNX2 and OSX gene expression and promotes the synthesis of specific non collagenous bone proteins, like BSP and OPN, it is likely that this nutrient is involved in triggering major events in osteogenesis and bone remodeling, potentially restoring the negatively affected balance of bone remodeling during aging. RUNX2 and OSX are indeed key transcription factors of osteoblastic differentiation which activate the downstream processes of osteoblast maturation [1519]; they also interact and coordinately regulate the expression of bone-specific genes [45]. Moreover, BSP and OPN are two non-collagenous proteins which serve as a matrix-associated signals presenting overlapping and multifunctional activities in bone with effects on bone formation, mineralization and remodeling [44].…”
Section: Discussionmentioning
confidence: 99%
“…Its restricted expression in osteocytes is achieved through an epigenetic mechanism; the SOST promoter is DNA methylated in osteoblasts but becomes demethylated during the osteoblast to osteocyte transition, allowing initiation of gene expression [30]. Transcription factors known to bind elements in the demethylated SOST promoter include the bone-specific transcription factors Runx2 and Osterix [31], [32]. Bone non-specific transcription factors such as MyoD and C/EBP also bind the SOST promoter in human Saos-2 cells [31].…”
Section: Mechanisms Underlying Sclerostin Down-regulation By Loadingmentioning
confidence: 99%
“…These results suggest that HDAC4 is required to maintain Runx2 expression after continuous PTH treatment. RUNX2 and OSX have been shown to regulate the SOST promoter in human cells …”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, deletion of HDAC4 in osteoblast lineage cells resulted in a significant inhibition of Sost expression by PTH. Sclerostin, a protein encoded by the Sost gene and expressed by osteocytes, inhibits osteoblastic bone formation . To confirm protein levels of sclerostin, we performed immunohistochemistry (IHC) and found that staining for sclerostin was stronger and the percentage of sclerostin‐positive osteocytes in Hdac4 ob‐/‐ mice was increased compared with Hdac4 fl/fl mice, and in these mice, PTH treatment caused a decrease in sclerostin staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation